Australian nursing and midwifery student beliefs and attitudes about domestic violence: A multi-site, cross-sectional study. (October 2019) - Doran, Frances; Hutchinson, Marie; Brown, Janie; East, Leah; Irwin, Pauletta; Mainey, Lydia; Mather, Carey; Miller, Andrea; van de Mortel, Thea; Sweet, Linda; Yates, Karen
Abstract: Nurses and midwives have a professional responsibility to identify and provide effective care to those experiencing domestic violence. Pre-registration preparation may develop this capability. In order to inform curriculum development, this study explored Australian nursing and midwifery students' attitudes and beliefs about domestic violence. Data were collected between June and October 2017. Descriptive statistics were calculated and comparative analysis performed on independent variables. Thematic analysis was performed on open-ended qualitative responses. Participants included 1076 students from nine Australian universities. The majority were enrolled in nursing programs (88.4%), followed by midwifery (8.6%), and combined nursing/midwifery (2.4%) programs. There was no statistically significant difference in scores by year level across all subscales, suggesting there was no developmental change in beliefs and attitudes toward domestic violence over the course of study. Nursing students held views that were more violence-tolerant than midwifery students. Australian and Chinese-born males were more likely to refute that domestic violence is more common against women. Students had a limited understanding of domestic violence suggesting a critical need to address undergraduate nursing and midwifery curricula. Highlights: Students are poorly prepared to recognise and respond to domestic violence. Nursing and midwifery students hold similar misperceptions about domestic violence. Nursing students appear more violent tolerant than midwifery students. Attitudes about domestic violence change little over the course of study. Attention toward curriculum and capability development is required.